Heading Frequency Is More Strongly Related to Cognitive Performance Than Unintentional Head Impacts in Amateur Soccer Players - Stewart, Walter F.; Kim, Namhee; Ifrah, Chloe; Sliwinski, Martin; Zimmerman, Molly E.; Kim, Mimi; Lipton, Richard B.; Lipton, Michael L. (Frontiers in Neurology, 2018)
Objective Compared to heading, unintentional head impacts (e.g., elbow to head, head to head, head to goalpost) in soccer are more strongly related to risk of moderate to very severe Central Nervous System (CNS) symptoms. But, most head impacts associated with CNS symptoms that occur in soccer are mild and are more strongly related to heading. We tested for a differential relation of heading and unintentional head impacts with neuropsychological (NP) test performance. Method Active adult amateur soccer players were recruited in New York City and the surrounding areas for this repeated measures longitudinal study of individuals who were enrolled if they had 5+ years of soccer play and were active playing soccer 6+ months/year. All participants completed a baseline validated questionnaire (“HeadCount-2w”), reporting 2-week recall of soccer activity, heading and unintentional head impacts. In addition, participants also completed NP tests of verbal learning, verbal memory, psychomotor speed, attention, and working memory. Most participants also completed one or more identical follow-up protocols (i.e., HeadCount-2w and NP tests) at 3- to 6-month intervals over a 2-year period. Repeated measures General Estimating Equations (GEE) linear models were used to determine if variation in NP tests at each visit was related to variation in either heading or unintentional head impacts in the 2-week period before testing. Results 308 players (78% male) completed 741 HeadCount-2w. Mean (median) heading/2-weeks was 50 (17) for men and 26 (7) for women. Heading was significantly associated with poorer performance on psychomotor speed (p < 0.001) and attention (p = 0.02) tasks and was borderline significant with poorer performance on the working memory (p = 0.06) task. Unintentional head impacts were not significantly associated with any NP test. Results did not differ after excluding 22 HeadCount-2w with reported concussive or borderline concussive symptoms. Conclusion Poorer NP test performance was consistently related to frequent heading during soccer practice and competition in the 2 weeks before testing. In contrast, unintentional head impacts incurred during soccer were not related to cognitive performance.